Peperoncini - Clauser, Marina; Grigioni, Andrea; Landi, Mario (Firenze University Press, 2010)
The chili pepper is a spice and medicinal remedy used since ancient times by the American peoples who were the first to undertake the domestication of 5 species belonging to the genus Capsicum (Solanaceae): Capsicum (Solanaceae): Capsicum annuum, C. baccatum, C. chinense, C. frutescens e C. pubescens. After the sixteenth century the chili pepper became similarly popular in other continents and today the five species number many reference pod-types and over 3,000 varieties. The book describes their uses in the different spheres of cuisine (aromatic, spicy and colourful), medicine (antioxidant and digestive for internal use, rubefacient and anti-rheumatic for external use) and ornamentation (cut branches, floral compositions, border plants, splashes of colour).